Improve Pronunciation With Vowel Sounds: - Tiara Adelia; Reinasya Boru Surbakti (Rahis Cendekia Indonesia, 2023)
Enhancing pronunciation through focused attention on vowel sounds is a transformative approach for language learners. This abstract explores the impact of targeted vowel training on improving overall oral communication skills. The study employs interactive exercises and feedback mechanisms to address nuances in vowel pronunciation. Participants engage in structured sessions, emphasizing vowel articulation, pitch modulation, and rhythm. Results indicate a discernible enhancement in clarity and intelligibility, showcasing the efficacy of this method in refining pronunciation. The findings underscore the significance of incorporating vowel-centric exercises into language education, offering a practical and impactful strategy for learners striving to achieve linguistic proficiency and effective communication.